Update on sex specific risk factors in cardiovascular disease - Nguyen, Andrew H.; Hurwitz, Madelyn; Sullivan, Scott A.; Saad, Antonio; Kennedy, Jamie L. W.; Sharma, Garima (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular disease (CVD) is the leading cause of death in the United States among both men and women. Women in particular face significant disparities in their cardiovascular care when compared to men, both in the diagnosis and treatment of CVD. Even when traditional risk factors for CVD are present, clinicians are more likely to attribute a lower perceived risk in women leading to worse outcomes. For example, hypertension is more prevalent among women and carries a two-fold higher mortality risk compared to men. Women with diabetes carry an excess risk of ischemic heart disease (IHD), and future risk of CVD by 3-7 fold versus 2-3 fold compared to men. Likewise, a recent meta-analysis demonstrated that tobacco use confers a 25% increased relative risk of major cardiovascular events in women when compared to men. These discrepancies in the relative risk of CVD when conventional risk factors are present appear to explain some, but not all, of the observed differences among men and women.